2010
DOI: 10.1159/000321518
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation Method of the Effect of Nattokinase on Carrageenan-Induced Tail Thrombosis in a Rat Model

Abstract: Thrombosis is characterized by congenital and acquired procatarxis. Nattokinase inhibits thrombus formation in vitro. However, in vivo evaluation of the therapeutic efficacy of nattokinase against thrombosis remains to be conducted. Subcutaneous nattokinase injections of 1 or 2 mg/ml were administered to the tails of rats. Subsequently, ĸ-carrageenan was intravenously administered to the tails at 12 h after nattokinase injections. The mean length of the infarcted regions in the tails of rats was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…This model has been extensively used to test the effect of several anti-thrombus and thrombolytic agents clinically (Yuan et al 2012;Yan et al 2009;Kamiya et al 2010;Simkhada et al 2012). Carrageenan is a linear sulphur containing polysaccharide, extracted from edible red seaweeds.…”
Section: Carrageenan-induced Thrombosis Modelmentioning
confidence: 99%
“…This model has been extensively used to test the effect of several anti-thrombus and thrombolytic agents clinically (Yuan et al 2012;Yan et al 2009;Kamiya et al 2010;Simkhada et al 2012). Carrageenan is a linear sulphur containing polysaccharide, extracted from edible red seaweeds.…”
Section: Carrageenan-induced Thrombosis Modelmentioning
confidence: 99%
“…Kamiya et al [10 ]suggested that thrombosis in the tail artery of rats could be used to evaluate the thrombolytic effect of nattokinase in vivo. Using this rat model, we aimed to determine whether nattokinase is thrombolytically active in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Among these enzymes, NK is assumed an interesting one. This considerable interest is due to the direct fibrinolytic activity of this enzyme, both in vitro and in vivo (Fujita et al 1995a;Kamiya et al 2010;Xu et al 2014). It not only degrades fibrin directly but also increases the release of tissue plasminogen activator from cells to degrade fibrin (Yatagai et al 2008).…”
Section: Fibrinolytic and Antithrombotic Activitymentioning
confidence: 99%